Semiconductor Optical Amplifiers and mm-Wave Wireless Links for Converged Access Networks - König, Swen (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2014)
Future access networks are converged optical-wireless networks, where fixed-line and wireless services share the same infrastructure. In this book, semiconductor optical amplifiers (SOA) and mm-wave wireless links are investigated, and their use in converged access networks is explored: SOAs compensate losses in the network, and thereby extend the network reach. Millimeter-wave wireless links substitute fiber links when cabling is not economical.